1981
DOI: 10.1063/1.328783
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric-to-paraelectric phase transition of vinylidene fluoride-trifluoroethylene copolymer

Abstract: A study of the ferroelectric phase transition of vinylidene fluoride-trifluoroethylene copolymers by ac calorimetryThe ferroelectric properties ofvinylidene fluoride-trifluoroethylene copolymer were studied. The infrared absorption spectra and x-ray diffraction patterns of the melt-crystallized film suggested the similar crystalline form to the polar form I of polyvinylidene fluoride. It was found that the ferroelectric-to-paraelectric phase transition occurred at 70 ·C and was the first order in the meltcryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(65 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…Subsequently, this peak was proven to correspond to the Curie point (Furukawa, Date, Fukada, Tajitsu and Chiba, 1980; Yamada, Ueda and Kitayama, 1981), and many detailed studies have been conducted from various viewpoints. In these copolymer samples, which differ from the case of PVDF, crystals of a ferroelectric nature can be obtained directly by melt-crystallization at atmospheric pressure without any mechanical or electrical treatments.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, this peak was proven to correspond to the Curie point (Furukawa, Date, Fukada, Tajitsu and Chiba, 1980; Yamada, Ueda and Kitayama, 1981), and many detailed studies have been conducted from various viewpoints. In these copolymer samples, which differ from the case of PVDF, crystals of a ferroelectric nature can be obtained directly by melt-crystallization at atmospheric pressure without any mechanical or electrical treatments.…”
Section: Introductionmentioning
confidence: 97%
“…Piezo-and pyroelecticity in ␤-PVDF results thus from alignment of dipoles by a static electric field and/or trapped charges injected during the poling process [3]. The ␤-PVDF structure is highly oriented; it has orthorhombic unit cells with a space group Cm2m (C 2v ) with a planar zig-zag (all-trans) chain conformation and parallel CF 2 dipole moments of the adjacent chains parallel to the crystallographic b-axis.…”
Section: Introductionmentioning
confidence: 99%
“…Some effort to characterize the ferro-to paraelectric transition in PVDF/F3Et copolymers as a function of temperature, mainly by means of WAXD, infrared and dielectric studies, has been reported [9][10][11][12][15][16][17]. There are still, however, some questions remaining concerning the understanding of the detailed microstructural mechanism through phase transformation.…”
Section: Discussionmentioning
confidence: 97%